Penerapan Asas Aman Dan Terbuka Terhadap Proses Pendaftaran Tanah - Anhar - (Fakultas Hukum Universitas Mataram, 2017)
Registration system of land in Indonesia adheres to the system negative berunsur positive. based system used it has the weaknesses. to reduce the risk of the use of the system is then in the government regulation No. 24 1997 on the land registry applied principle safe and open in the land registry. although the principle that has been applied but still there are problems regarding the certificate of land rights are published. in Indonesia is still a lot of certificate issued a lot of problems and sued in court. especially in the district Lombok Western, in the area sekotong there land 100 acres of certified double contested entrepreneur Bali and Jakarta.